The Impact of Rising Food Prices on the Households in a Low Income Township in South Africa - Sekhampu, Tshediso Joseph; Dubihlela, Dorah (Mediterranean Journal of Social Sciences, 2012)
Food prices in South Africa have increased significantly in recent years. The impact of these price increases on manyresidents remains largely unknown. The study reported here analyzed the perceptions of households in a low income township ofBophelong (South Africa) in order to assess the impact of increases in food prices. The results are based on a household survey usingquestionnaires. The majority of households reported that they do not have enough income to meet their daily needs. The increase inprices in general was much higher for electricity and commuting. A logistic regression model was used to determine the socio-economicfactors affecting the reported impact of increase in food prices. Married and employed household heads reported lower severity levels.Female-headed households reported higher severity levels of price increases. Household income, household size, age, educationalattainment of the household head and the labour- force had no effect on the reported impact of prices. The article provides usefulinformation to policy makers by providing information on the reported impact of rising food prices among low income households in aSouth African context.